3D mechanical modeling of soil orthogonal cutting under a single reamer cutter based on Drucker–Prager criterion - Zhu, X.H.; Jia, Y.J. (Tunnelling and underground space technology, 2014)
•Basing on D-P criterion, a 3D analytical cutting force model of soil orthogonal is proposed.•The reaming efficiency of reamer is analyzed based on 3D analytical cutting force model.•The results can provide a guideline to the appliction and design of the reamer for various soils. Reamers have been the major implement used to enlarge the hole size in reaming stage of horizontal directional drilling (HDD). The choice of its available structural design becomes critical to maximize the rate of penetration and minimize the tripping time, thereby decreasing the cost of operations and the risk of experiencing stability problems. Moreover, because the duration period of a HDD project is largely dependent on the reaming stage, it is crucial to study the reaming efficiency by use of the appropriate operating conditions (cutting angle and depth). In the paper, the reaming efficiency of reamer is analyzed based on the development of a 3D analytical cutting force model of soil orthogonal cutting under a single reamer cutter. Focusing on the soil orthogonal cutting mechanism under a single reamer cutter, the interaction and friction between soil and cutter and the shear action of 3D shear zone are comprehensively considered, consequently the mechanical properties are given. Based on these analyses and using the Drucker–Prager criterion given a weight to the intermediate principal stress, the analytical models are proposed. In addition, this paper presents 3D FEM simulations for the analysis of soil orthogonal cutting under a single reamer cutter. The subject has been covered in two parts. Part one deals with the verification of the analytical cutting force model, the other focuses on the assessment and selection of the criterions of shear angle. The analytical cutting force model presented provides the capability to evaluate cutter loading for utilization of a single cutter with different rake angles to cut soils, and to plot the effect of change in the rake angle. Finally, the optimum rake angle of single reamer cutter was obtained. The results of this analysis can be integrated to study reamer performance. It can also provide a guideline to the application and design of the reamer assembly for various soils.